1988
DOI: 10.1037/0882-7974.3.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning of the eyeblink response in the delay paradigm in adults aged 18–83 years.

Abstract: To determine if age differences in classical conditioning of the eyelid response begin to appear in middle age in humans as they do in animals, adult subjects aged 18-83 years were trained in the delay conditioning paradigm. Large age effects occurred. Statistically significant differences first appeared in the decade of the 40s. Within-age-group variability was large. To reduce variability, subjects were classified by the magnitude of their unconditioned response (UR). Regardless of age, subjects with low amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
133
6

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(163 citation statements)
references
References 28 publications
24
133
6
Order By: Relevance
“…These findings provided evidence that this age-related deleterious process occurs much earlier and that some cognitive abilities exhibit a dramatic decline between 8 and 11 months of age, consistent with one human study (28). From our survey of the literature, it appears that very few reports of animal studies have described changes in learning and memory during this period.…”
Section: Discussionsupporting
confidence: 66%
“…These findings provided evidence that this age-related deleterious process occurs much earlier and that some cognitive abilities exhibit a dramatic decline between 8 and 11 months of age, consistent with one human study (28). From our survey of the literature, it appears that very few reports of animal studies have described changes in learning and memory during this period.…”
Section: Discussionsupporting
confidence: 66%
“…Woodruff-Pak and Thompson (1988) found similar results in their younger participants trained on delay conditioning (learning progressed from 40% to 80% CRs over the first 72 trials). Therefore, rapid rates of learning were expected in the age group we examined (the mean age of the normal control participants was in the mid-40s; Patient B.R.…”
Section: Conditioningsupporting
confidence: 63%
“…Several studies have shown impaired conditioning with increasing age (Bellebaum & Daum, 2004;Knuttinen, Power, Preston, & Disterhoft, 2001;LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;Solomon, Pomerleau, Bennett, James, & Morse, 1989;Woodruff-Pak & Thompson, 1988). In the present study, the age (61 years) of one member of the trace group fell in a range that has previously shown impairment relative to younger subjects (Bellebaum & Daum, 2004;LaBar et al, 2004).…”
Section: Discussionmentioning
confidence: 58%